2017
DOI: 10.17265/2328-2150/2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Study of Some Biological Active Compounds in the Sea-Buckthorn (Hippophae rhamnoides.L) Berries

Abstract: Abstract:In Mongolia, the sea buckthorn is a nontraditional fruit crop. It has been being planted since 2000 in the Botanical garden of Medicinal plants of Monos group, Mongolia. The purpose of this study was to determine how to change biological active compounds in the Sea-buckthorn berries that depending on harvesting season and to describe which harvesting period is efficient to use. In 2013-2014, fruit samples were prepared from our botanical garden such as: Chuiskaya, Maslichnaya, Vitaminnaya, Oranjivaya,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…β-carotene, organic acids, essential oils, polyphenols, flavonoids, phytosterols, tocopherols, vitamins (K, C, E, B complex), polyunsaturated fatty acids, coumarins, triterpens, protein (globulins, albumins), amino acids, carbohydrates, minerals (N, Ca, K, Na, Mg, Cu, Fe, Zn, Mn) [44][45][46] Hypericum Hypericum perforatum L.…”
Section: Active Compounds Referencesmentioning
confidence: 99%
“…β-carotene, organic acids, essential oils, polyphenols, flavonoids, phytosterols, tocopherols, vitamins (K, C, E, B complex), polyunsaturated fatty acids, coumarins, triterpens, protein (globulins, albumins), amino acids, carbohydrates, minerals (N, Ca, K, Na, Mg, Cu, Fe, Zn, Mn) [44][45][46] Hypericum Hypericum perforatum L.…”
Section: Active Compounds Referencesmentioning
confidence: 99%
“…Research has shown that seabuckthorn fruits contain a number of valuable biologically active substances such as β—carotene, organic acids, essential oils, polyphenols, flavonoids, phytosterols, tocopherols, vitamins, polyunsaturated fatty acids, coumarins, triterpens, protein (globulins, albumins), amino acids, carbohydrates, minerals [ 6 , 7 ]. These active compounds play a very important role in regulating the human metabolism, with therapeutic and curative action in the prevention and treatment of eye and skin diseases, juvenile acne, gastroenteritis, chronic hepatitis, kidney impairment, high blood pressure, avitaminosis, diseases of the nervous system, burns, etc.…”
Section: Introductionmentioning
confidence: 99%